Respons Pertumbuhan dan Hasil Kedelai (Glycine Max L.) terhadap Aplikasi Kascing pada Kondisi Cekaman Kekeringan di Tanah Ultisol - Ari Andani Nasution; Zul Fahmi; Endah Cahyani Simamora (CV. ALIM'SPUBLISHING, 2026)
Ultisol soil has limited fertility and low water-holding capacity, making it susceptible to drought stress in soybean cultivation. The application of kascing organic fertilizer has the potential to improve the soil's physical and chemical properties and enhance the plants' tolerance to water stress. This study aims to analyze the effect of kascing doses on soybean growth and yield under varying levels of drought stress in Ultisol soil. The study used a two-factor factorial Randomized Block Design (RBD) with three replications. The first factor was cassava dosage (0, 5, and 10 tons ha⁻¹) and the second factor was drought stress levels (100%, 75%, and 50% of field capacity). Observed parameters included plant height, number of leaves, number of pods per plant, seed weight per plant, seed yield per hectare, and soil organic matter content. Data were analyzed using ANOVA and the 5% LSD test. Research results show that the application of composting increases soybean growth and yield significantly. Drought stress reduces productivity, but the application of composting can mitigate the negative effects of drought. The combination of 10 tons ha⁻¹ of composting at 75% field capacity produced the highest productivity of 3.42 tons ha⁻¹.